Concentration of Heavy Metals in Available Fish Species (Bain, Mastacembelus armatus; Taki, Channa punctatus and Bele, Glossogobius giuris) in the Turag River, Bangladesh: Heavy Metal Concentration in Bangladesh Fish (Biological Sciences - PJSIR, 2015)
This study was conducted to assess the concentration level of heavy metals in three available fish species (Bain, Mastacembelus armatus; Taki, Channa punctatus and Bele, Glossogobius giuris) of the Turag river, Bangladesh during the months from January to March, 2014. In case of bio-concentration of heavy metals in fish, the levels of Pb, Cd, Cr, Cu and Fe ranged from 0.01-0.13 mg/kg, 0.001-0.02 mg/kg, 0.17-0.48 mg/kg, 0.30-0.74 mg/kg and 4.05-46.86 mg/kg, respectively while Hg was below detection level. These values indicate that the heavy metals were concentrated in fish flesh at a higher level than water. The highest values of Pb, Cd and Cr were found in Bain fish, Fe was found in Taki fish and Cu was found in Bele fish. Most of the heavy metals have crossed the permissible limits in fish, especially for the values of Cr, Cu and Fe. From the results of the present investigation, it can be concluded that the available fish species are harmful for their consumers.